On the Origin of ULF Magnetic Waves Before the Taiwan Chi-Chi 1999 Earthquake - Anagnostopoulos, Georgios (Frontiers in Earth Science, 2021)
The ultra low frequency (ULF) electromagnetic (EM) wave activity usually recorded on Earth’s ground has been found to depend on various types of space weather. In addition ULF waves observed before an earthquake have been hypothesized to be a result of geotectonic processes. In this study we elaborate for the first time the origin of sub-ULF (<1msec) magnetic field waves before an earthquake (Chi-Chi / Taiwan, 20.9.1999) by comparing simultaneously obtained measurements in the interplanetary space (ACE satellite) and on the Earth’s ground (Taiwan). The most striking result of our data analysis, during a period of 7 weeks, is that the detection of four groups of sub-ULF waves in Taiwan coincide in time with the quasi-periodic detection of two solar wind streams by the satellite ACE with approximately the solar rotation period (~28 days). The high speed solar wind streams (HSSs) in the interplanetary space were accompanied by sub-ULF Alfvѐn wave activity, quasi-periodic southward IMF and solar wind density perturbations, which are known as triggering agents of magnetic storm activity. The four HSSs were followed by long lasting decreases in the magnetic field in Taiwan. The whole data set examined in this study strongly suggest that the sub-ULF magnetic field waves observed in Taiwan before the Chi-Chi 1999 earthquake is a normal consequence of the incident of HSSs to the magnetosphere. We provide some observational evidence that the sub-ULF electromagnetic radiation on the Earth was most probably a partner to (not a result of) geotectonic processes preparing the Taiwan 1999 earthquake.